We are caught up in our own world : conceptions of curriculum within three different disciplines at the University of Iceland - Guðrún Geirsdóttir (2009)
Menntunarfræði This study explores the conceptions that university teachers have of curriculum decision making and development within three different disciplines and the space and agency of teachers in the curriculum process. The study makes use of Basil Bernstein’s concepts of the classification and framing of the pedagogic discourse of higher education disciplines and applies them to the pedagogic discourse of three disciplines (i.e. mechanical and industrial engineering, anthropology and physics) to demonstrate how it appears in traditions, communication and planning of instruction. The three disciplines were explored as specific cases. Data were collected through interviews, observations and analysis of texts. Fifteen university teachers were interviewed, eight staff meetings observed and a variety of texts analysed. Mixed phenomenological methods of data analysis such as looking for common themes and discourse analysis were applied. The main findings of the study are the existence of a local pedagogic discourse of each discipline, characterised by different aims of the discipline, different conceptions of student identities and teacher roles, and specific instructional discourse. The local pedagogic discourse is created when a universal pedagogic discourse is recontextualised within a local socio-cultural context. The transformation creates spaces for different ideologies (personal, disciplinary, institutional and external). In the transformation process, the university teachers hold a significant and powerful role. The local pedagogic discourse is most strongly influenced by teacher conceptions acquired during their own time of studying the discipline and their experience of teaching. The discipline’s organisational culture and structure as well as its saga both mould the local pedagogic discourse and create its social context within which different contesting ideologies arise. Internal and external ideologies, such as the University’s research mission, influence the disciplinary ideologies in different ...